Application of Python for Analysis and Visualisation of ChatGPT User Dataset on College Students - Citra Andhini Rizkitha; Wahyu Supriyatin; Yasman Rianto (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
ChatGPT is an artificial intelligence supported by AI intelligence that allows textual conversational interaction. It is a versatile tool that can be used by various groups of people, including students. Students use ChatGPT to find information in support of their lecture activities. The increasing number of ChatGPT users among students has prompted research into analysis and visualisation of ChatGPT users in students. This study aims to conduct analysis and visualisation of ChatGPT users among students, both IT and non-IT students. The analysis is done to see whether ChatGPT can help and provide information to students. The results of the analysis will be displayed in the form of visualisation using bar charts so that the information conveyed is easy to see. The dataset used in the study was obtained from primary data through a questionnaire conducted to 80 respondents with 16 questions. In this research, qualitative analysis methods and data visualisation techniques were employed. The dataset obtained is then subjected to a process of cleaning to avoid data duplication and the inclusion of inappropriate data. Subsequent to the cleansing of the dataset, the data analysis process and data visualisation are then carried out. The analysis yielded several notable findings. Firstly, it was revealed that 85% of respondents were aware of ChatGPT, and furthermore, 75% of respondents expressed feeling assisted by its existence. However, 66% of respondents expressed reservations about immediate trust in the generated responses, and 60% indicated a lack of complete reliance on ChatGPT. Future research endeavours may explore the use of visualisation tools such as Looker Studio, Microsoft Power BI, or Tableau. Secondary data can be obtained from the Kaggle website, which contains a more varied range of data.